Carbon Credit Project Financing through Productive Waqf and Corporate Social Responsibility - Syahrir Akbar; Rehan Perdana Putra; Novriyanti (AL-ARBAH: Journal of Islamic Finance and Banking, 2026)
Purpose - This study aims to develop an alternative financing model that integrates productive waqf and CSR to support sustainable carbon credit projects as a response to the climate crisis. Method - The study adopts a qualitative descriptive approach using a literature review. Data are analyzed through thematic analysis, SWOT analysis, and meta-synthesis to identify key patterns, strategic positioning, and conceptual integration of carbon credit financing. Result - The findings indicate that Indonesia’s carbon credit ecosystem has substantial growth potential, particularly for NbS projects. Carbon credit projects can be classified based on their characteristics and emission reduction capacity. Integrating productive waqf instruments, such as CWLS and CWLD, with CSR funding offers a sharia-compliant and sustainable financing model. Although challenges remain, including bureaucratic complexity and public trust issues, strong government support and Indonesia’s large waqf potential provide significant implementation opportunities. From a sharia perspective, the application of ba’i al-huquq al-ma’nawiyah supports the permissibility of carbon trading. Implication - This model offers strategic guidance for governments, CSR-oriented firms, financial authorities, and nazir institutions to mobilize Islamic social finance for environmental protection and climate mitigation. Originality - This research proposes a carbon credit financing model by uniquely integrating productive waqf with CSR in a practical and sustainable ecosystem. Keywords: Carbon Project, Productive Waqf, Corporate Social Responsibility, Finance